Chinese opera cultural center as a medium of expressing the cultural identity in Chinatown, Kuala Lumpur [electronic resource] - Chia, Gin Jiah, 1991-, author 605144; Wan Hashimah Wan Ismail, supervisor 605145; Syed Ahmad Iskandar Syed Ariffin, supervisor 273150; Fakulti Alam Bina 8041 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2016